Development of NutriA, a mobile application to enhance nutritional awareness in older adults: G. Viroli,1 F. Bolpagni,2-4 N. Madini,1 C. Ricciardi Rizzo,1 S. Santero,1 A. Vincenti,1 P. Bosoni,5 D. Pala,6 G. Lanzola,5 S. Quaglini,5 H. Cena1,2 | 1Laboratory of Dietetics and Clinical Nutrition, Department of Public Health, Experimental and Forensic Medicine, University of Pavia; 2Istituti Clinici Scientifici Maugeri IRCCS, Unit of Clinical Nutrition, Pavia; 3National Biodiversity Future Center, Palermo; 4Department of Earth and Marine Sciences, University of Palermo; 5Department of Electrical, Computer and Biomedical Engineering, University of Pavia; 6Department of Management, Information and Production Engineering, University of Bergamo, Italy (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2026)
Although Mhealth can support geriatric care, few applications specifically address malnutrition.1 NutriA Senior is a mobile app designed to increase food knowledge and support diet adherence in frail older adults.2 It includes 48 interactive quizzes with feedback and gamification to promote active learning, along with 24 boxes providing in-depth explanations and suggesting simple daily actions to foster behavior changes. Topics address nutritional knowledge, food safety, sustainability, non-communicable diseases, and food labeling. NutriA was designed as a simple and self-instructing App3 on the Moodle platform. A usability study involving 40 older adults suggests the App’s feasibility and potential, which will be further evaluated in a clinical trial involving frail older individuals. With population ageing, such technology may provide valuable support to clinicians in delivering personalized nutritional treatment.*****Funding: this research was funded under the National Recovery and Resilience Plan (NRRP), Mission 4 Component 2 Investment 1.3—Call for tender No. 341 of 15 March 2022 of the Italian Ministry of University and Research, funded by the European Union—NextGenerationEU. Project code PE00000003, Concession Decree No. 1550 of 11 October 2022, adopted by the Italian Ministry of University and Research, CUP F13C22001210007, Project title “ON Foods—Research and innovation network on food and nutrition Sustainability, Safety and Security—Working ON Foods”.